Influência de ligantes ancilares na inserção de complexos de rutênio em proteína aplicada ao desenvolvimento de sensores amperométricos - Silva, Ronnie Edson da (2014)
Three new ruthenium complexes of general formula [Ru(PAN)(PPh3)2L]PF6 were synthesized and characterized by RMN 1H techniques and UV/Visible . The interaction of the complex with bovine serum albumin spectra was monitored by fluorescence quenching. The trends of the values contained suppression Stern-Volmer (Ksv) as a function of temperature indicate possible mechanisms for interaction of these three complexes with the macromolecule , where: i) static mechanism for systems containing derivatives [Ru(PAN)(PPh3)2 (MeIM )]+ and [Ru(PAN)(PPh3)2(4,4'-Bpy)]+; ii) dynamic mechanism for the system containing the derivative [Ru(PAN)(PPh3)2(ISN)]+. The thermodynamic parameters (?H, ?S e ?G) associated with the interaction BSA-ruthenium complex indicated that the cases were spontaneous and character of binding was hydrophobic forces involved for the system containing the ancillary ligand isonicotinamide (ISN) and to electrostatic systems containing the ancillary ligands methylimidazole (MeIM) and 4,4'-bipyridine (4,4'-Bpy) . The use of ibuprofen probe coupled with thermodynamic parameters, allowed us to infer the possible location of the ruthenium complexes in the biomolecule. In this case, the complex containing the ancillary ligand isonicotinamide (ISN) was encapsulated into a more hydrophobic internal cavity near the tryptophan residue 212, while the complex containing the ancillary ligands methylimidazole (MeIM) and 4,4'-bipyridine (4,4'-Bpy ) were housed in a more superficial region of the protein , near the tryptophan residue 134. Preliminary experiments involving electroanalytical the surface modification of electrodes FTO bovine albumin serum and ruthenium complex have revealed the potential of these systems as for amperometric detection of ascorbic acid in aqueous solution and in the presence of dopamine sensors